College Algebra (11th Edition)

Published by Pearson
ISBN 10: 0321671791
ISBN 13: 978-0-32167-179-0

Chapter 1 - Section 1.4 - Quadratic Equations - 1.4 Exercises - Page 112: 63


$x=\left\{ \dfrac{-3-\sqrt{41}}{8},\dfrac{-3+\sqrt{41}}{8} \right\}$

Work Step by Step

$\bf{\text{Solution Outline:}}$ To solve the given equation, $ (4x-1)(x+2)=4x ,$ use the FOIL Method and express the equation in the form $ax^2+bx+c=0.$ Then use the Quadratic Formula. $\bf{\text{Solution Details:}}$ Using the FOIL Method which is given by $(a+b)(c+d)=ac+ad+bc+bd,$ the expression above is equivalent to\begin{array}{l}\require{cancel} 4x(x)+4x(2)-1(x)-1(2)=4x \\\\= 4x^2+8x-x-2=4x \\\\= 4x^2+(8x-x-4x)-2=0 \\\\= 4x^2+3x-2=0 .\end{array} In the equation above, $a= 4 ,$ $b= 3 ,$ and $c= -2 .$ Using the Quadratic Formula which is given by $x=\dfrac{-b\pm\sqrt{b^2-4ac}}{2a},$ then \begin{array}{l}\require{cancel} x=\dfrac{-3\pm\sqrt{3^2-4(4)(-2)}}{2(4)} \\\\ x=\dfrac{-3\pm\sqrt{9+32}}{8} \\\\ x=\dfrac{-3\pm\sqrt{41}}{8} .\end{array} The solutions are $ x=\left\{ \dfrac{-3-\sqrt{41}}{8},\dfrac{-3+\sqrt{41}}{8} \right\} .$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.